Eosinophil functions in allergic diseases: an evolving paradigm - Spencer, Lisa A. (Henry Stewart Talks, 2020)
Eosinophil morphology, development, and tissue distribution in health, Mechanisms of eosinophil tissue recruitment in allergic diseases, Eosinophil effector functions: Exocytosis and the traditional paradigm, Eosinophil modes of degranulation revisited, Eosinophil effector functions: Piecemeal degranulation and an evolving paradigm, Release of eosinophil extracellular granules and DNA traps